Re-foundational Syncretism between Christianity and Islam: the Cartographies of the Grenadian Sacromonte, XVI and XVII centuries - Francisco Antonio García Pérez (Disegnare con, 2020)
The discovery of the renowned Lead Books and a series of supposed martyr's relics in a hill outside the walls of Granada  in the last years of the XVII century was the last attempt of the morisco elite to ensure their permanence in the recently Christianized city. These findings, totally invented by this Islamic minority sector, did not give the expected result, but they served the Christian community to reformulate the image of their city, signifying it within the new counter-reformist context. From these facts, a series of cartographic etchings were made that tried to eloquently manifest the Christian excellence of the city.  The aim of this paper is to articulate an original analytic description of five of these drawings. It will be possible to recognize that the composition and graphic coding strategies that were used in the making of the maps made them an optimal instrument for expressing the renewed sacred dimension of the city and its territory. DOI: https://doi.org/10.20365/disegnarecon.25.2020.15